Perbandingan Stok Karbon Berbasis Penggunaan Lahan dan Rencana Pola Ruang pada Wilayah Perencanaan III Kota Singkawang: Comparison of Carbon Stock Based on Land Use and Spatial Pattern Plans in Planning Area III of Singkawang - Siska Ita Selvia; Taufiqurrahman Taufiqurrahman; M. Irvan Kurnia (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Climate change is a strategic global issue and its concern to many regions in Indonesia because it will impact the sustainability of many sectors. One of the causes of climate change is the existence of Green House Gases (GHG), especially carbon dioxide (CO2), which has the highest concentration in the atmosphere due to human activities. Massive development activities have caused the dynamics of changes in land use from undeveloped land to built-up land. Singkawang City Singkawang City has a population that continues to increase, namely in the period 2010-2020 it has a population growth rate of 2.27%. This of course can trigger a conflict of space requirements that are not proportional to the availability of existing land. Planning Area (WP) III of Singkawang City, which currently has a higher proportion of undeveloped land than built-up land, will faced challenges, due to the many development plans such as airports, industrial allotment areas and other supporting facilities. Of course, this will triggered changes in land use functions which can reduce carbon stocks. Therefore, the purpose of this study is to compare carbon stocks based on existing land use classes and the area of each type of money polar plan according to the Detailed Spatial Plan (RDTR) of WP III. The analytical method used is to analyze carbon stocks using conversions from the 2012 Directorate General of Forestry Planning standards and using the GHG calculator developed by ICLEI-Local Governments for Sustainability. The result of this study is that there is a decrease in carbon stocks in the spatial pattern plan (233.267,15 tons C) compared to carbon stocks based on the existing land use class in WP III (236.224,78 tons C). This shows that there is a difference of 2.957,63 tonnes C or a decrease in carbon stocks of 1,3%.